Apparitions of Virgin Mary: Sociological Analysis - Liutikas, Darius (Sociologija. Mintis ir veiksmas, 2019)
The main purpose of this article is to discuss the social aspects of the apparitions of the Virgin Mary, the development of apparition places, as well as the motivation and behavioral characteristics of pilgrims going to the miraculous places of the Virgin Mary in Lithuania. The article reviews the criteria recognized by the Church for assessment of the authenticity of apparitions, their characteristics, paradigm, and other scientific researches, a list of the Vatican-approved apparitions and apparition places in Lithuania. We used the main elements of the paradigm of apparitions for an empirical study of the officially recognized apparition in Šiluva, Lithuania. Finally, we also explore the complex motivation of religious tourism and pilgrimage. It relates to the manifestation of pilgrims’ personal or community values and identity as well as other cognitive or social motives. The paper concludes that the apparitions of the Virgin Mary take place in locations where social groups resist political, social, or moral change. Therefore, places of apparitions become a continuously re-created and re-interpreted social reality.